Penerapan Model Pembelajaran SSCS (Search, Solve, Create, and Share) Terhadap Peningkatan Kemampuan Pemecahan Masalah Siswa pada Materi Bangun Ruang Siswa Kelas V SD Negeri Ungaran 02 - Fina, Jayanti; Putra, Lisa Virdinarti (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2023)
This purpose of this research was to know the effectiveness of the SSCS learning model (search, solve, create, and share) on problem solving abilities of the fiveth grade students in SD Negeri Ungaran 02. The type of this research was an experiment with a nonequivalent control group design. The population in this research was all students in Public Elementary School Ungaran 02 and the research sample was the 5th -grade students in Public Elementary School Ungaran 02. The data was analyzed by normality test, homogenity test, simple liniear regression test, independent sample t test, and paired sample t test. The result resulted : There is an increase in the application of the SSCS learning model to students' problem solving abilities in class V SD Negeri Ungaran 02 as evidenced by a significance value 0.05, namely 0.000 0.05 using the paired sample t test.